Genome-wide analysis reveals the ancient and recent admixture history of East African Shorthorn Zebu from Western Kenya - Mbole-Kariuki, Mary N.; Sonstegard, T.S.; Orth, Alan S.; Thumbi, Samuel M.; Bronsvoort, B.M. de C.; Kiara, Henry K.; Toye, Philip G.; Conradie, I.; Jennings, A.; Coetzer, K.; Woolhouse, Mark E.J.; Hanotte, Olivier H.; et al. (Springer, 2014)
The Kenyan East African zebu cattle are valuable and widely used genetic resources. Previous studies using microsatellite loci revealed the complex history of these populations with the presence of taurine and zebu genetic backgrounds. Here, we estimate at genome-wide level the genetic composition and population structure of the East African Shorthorn Zebu (EASZ) of western Kenya. A total of 548 EASZ from 20 sub-locations were genotyped using the Illumina BovineSNP50 v. 1 beadchip. STRUCTURE analysis reveals admixture with Asian zebu, African and European taurine cattle. The EASZ were separated into three categories: substantial (⩾12.5%), moderate (1.56%<12.5%) and non-introgressed (⩽1.56%) according to the European taurine genetic proportion. The non-European taurine introgressed animals (n=425) show an unfluctuating zebu and taurine ancestry of 0.84±0.009 s.d. and 0.16±0.009 s.d., respectively, with significant differences in African taurine (AT) and Asian zebu backgrounds across chromosomes (P<0.0001). In contrast, no such differences are observed for the European taurine ancestry (P=0.1357). Excluding European introgressed animals, low and nonsignificant genetic differentiation and isolation by distance are observed among sub-locations (Fst=0.0033, P=0.09; r=0.155, P=0.07). Following a short population expansion, a major reduction in effective population size (Ne) is observed from approximately 240 years ago to present time. Our results support ancient zebu × AT admixture in the EASZ population, subsequently shaped by selection and/or genetic drift, followed by a more recent exotic European cattle introgression.